2020
DOI: 10.1002/jsp2.1131
|View full text |Cite
|
Sign up to set email alerts
|

The effects of 3D culture on the expansion and maintenance of nucleus pulposus progenitor cell multipotency

Abstract: Introduction: Low back pain (LBP) is a global health concern. Increasing evidence implicates intervertebral disk (IVD) degeneration as a major contributor. In this respect, tissue-specific progenitors may play a crucial role in tissue regeneration, as these cells are perfectly adapted to their niche. Recently, a novel progenitor cell population was described in the nucleus pulposus (NP) that is positive for Tie2 marker. These cells have self-renewal capacity and in vitro multipotency potential. However, extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 78 publications
0
29
0
Order By: Relevance
“…For example, FGF2-stimulated WTC culture increased the final Tie2 + fraction 7.5-fold compared with standard PCC. Comparatively, work by Guerrero et al [ 26 ] revealed a 1.8-fold increase in Tie2 rates, comparing their human NP cells cultured in alginate bead versus a standard monolayer culture. A 3.6-fold increase was reported by Zhang et al [ 30 ], who employed spheroid-based suspension cultures.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, FGF2-stimulated WTC culture increased the final Tie2 + fraction 7.5-fold compared with standard PCC. Comparatively, work by Guerrero et al [ 26 ] revealed a 1.8-fold increase in Tie2 rates, comparing their human NP cells cultured in alginate bead versus a standard monolayer culture. A 3.6-fold increase was reported by Zhang et al [ 30 ], who employed spheroid-based suspension cultures.…”
Section: Discussionmentioning
confidence: 98%
“…These Tie2 + cells were characterized as undifferentiated cells with multipotency and possessing high self-renewal abilities [ 22 , 23 , 24 , 25 ]. Therefore, we and others have proposed Tie2 + NPPC as a potent cell source for regenerative cell therapies against IVD degeneration [ 26 ]. However, their utilization is hindered by low Tie2-expressing cell yields from NP tissue, in particular from commonly available older and degenerated tissue sources [ 21 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The classic and common culture conditions are based on 2D culture and normoxic environment [13][14][15]. In this research, we primarily wanted to compare the impact of chemical treatments on the Tie2+ NPPCs population [16,17]. For this reason, the cells were cultured within a normoxic environment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, new protocols for (i) how to maintain the number of initially cell-sorted NPPCs in cell culture and (ii) the protection of their stemness are urgently warranted. Recent work could clearly demonstrate that changing the expansion protocol from 2D to 3D can indeed increase the Tie2+ cell's yield [16,17]. Moreover, NPPC protection through molecular injection could rebuild the cell's homeostasis in IVDD; it could evolve as a new approach for IVDD therapy.…”
Section: Introduction 1nucleus Pulposus Cells and Their Progenitorsmentioning
confidence: 99%